2018
DOI: 10.1182/blood-2018-99-113220
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose of Human scFv-Derived BCMA-Targeted CAR-T Cells Achieved Fast Response and High Complete Remission in Patients with Relapsed/Refractory Multiple Myeloma

Abstract: Introduction: B Cell Mature Antigen (BCMA)-targeted chimeric antigen receptor T (CAR-T) cell therapy emerges as promising treatment for patients with relapse/refractory multiple myeloma (RRMM). Previous studies indicate patients who receive high-dose CAR-T cells may achieve better remission but have worse adverse events, like cytokine release syndrome (CRS). To solve this dilemma, we have developed novel autologous CAR-T therapeutics CT053 that are genetically modified T cells comprising an extracellular anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…This was pooled from 11 studies involving 197 evaluable patients of whom 35 showed neurological adverse events. Peak CAR T-cell expansion appeared to be more likely in the setting of more severe CRS in three studies 37,38,42 but was not associated with adverse events in one study. 31 Most hematologic toxic effects of grade 3 or higher were neutropenia (85%), thrombocytopenia (70%), and leukopenia (60%).…”
Section: Safetymentioning
confidence: 97%
See 4 more Smart Citations
“…This was pooled from 11 studies involving 197 evaluable patients of whom 35 showed neurological adverse events. Peak CAR T-cell expansion appeared to be more likely in the setting of more severe CRS in three studies 37,38,42 but was not associated with adverse events in one study. 31 Most hematologic toxic effects of grade 3 or higher were neutropenia (85%), thrombocytopenia (70%), and leukopenia (60%).…”
Section: Safetymentioning
confidence: 97%
“…The baseline characteristics of the included studies are listed in Table 1. A total of 314 patients were included in the 18 studies, [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] all of which were single-arm early phase studies that included only patients with RRMM (17 studies) or newly diagnosed myeloma (1 study). Patients included in RRMM studies were heavily pretreated and received a median of 6 prior lines of treatment (proteasome inhibitors, immunomodulatory drugs, monoclonal antibodies, 1-2 autologous stem cell transplants).…”
Section: Patient and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations